The Study of Clinical Application and Anticancer Mechanism of Alpha-lactalbumin and Oleic Acid Composition - Pooneh Mokarram; Hamid Behrouj; Sedigheh Rezayi; Morvarid Siri (مجله علوم پزشکی صدرا, 2019)
Milk protein, alpha-lactalbumin, is one of the proteins that many researchers have done a lot of research on its structure and function. In the late nineties, a completely different activity of α-LA was discovered. When α-LA is present in a conformation that has been partially unfolded, it can form a complex with oleic acid (OA), which specifically has an anti-cancer activity. The complex between human α-LA and OA has been called HAMLET (Human Alpha-lactalbumin Made LEthal to Tumor cells). The cell death mechanism by HAMLET has not yet been determined. However, it has been shown that HAMLET interacts with various cellular organelles including nuclei, lysosomes, mitochondria, proteases, and ribosomes. Apoptosis, autophagy, and disorders in the structure of chromatin are three different cytotoxic pathways activated in response to HAMLET. In this study, a summary of the structure, antitumor mechanisms, and clinical applications of this complex will be presented.